An Evaluation of the Implications of Intra-Urban Migration on Residential Real Estate Market in Asaba, Delta State, Nigeria - Adjekophori, B.; Emoh, F. I.; Osagioduwa, M. (International Journal of Real Estate, 2025)
Migration dynamics remain one of the daunting hydra-headed challenges confronting contemporary African cities in the 21st century. This study investigates the implications of intra-urban migration on residential real estate market with a view to ascertaining the factors influencing intra-urban migrations and the extent to which it affects residential real estate submarket in Asaba, Nigeria. The study adopted a descriptive research design. A 5-point Likert scale questionnaire was developed and administered on 133 participants which comprise of 121 household head and 12 registered Estate Surveyors and Valuers firm in the city of Asaba. The systematic, random and purposive sampling techniques were used in the selection of the participants. Data collected were captured in statistical package for social science (SPSS Version 23) and were analyzed using Relative Impact Index (RII) and Factor Analysis (FA). Results of the study found that social environment, accessibility, employment were the major factors influencing intra-urban movement. It also discovered that deterioration of infrastructural facilities as a result of over population, increase in the demand for residential property and increase the level of urban consumption were the most important effects of intra-urban migration on Asaba residential submarket. The study therefore recommends that governments at all level should provide social infrastructures and employment opportunities to improve the quality of life and discourage intra-urban movement within the city. Investors should take advantage of the situation and invest heavily in residential real estate in other to secure maximum return on investment. States and local government should get ready with better strategies to increase housing supply and infrastructural provision and improvement in strategic location around the city to control the level of intra-urban migration in Asaba.
Keywords: Asaba; Intra-Urban; Migration; Real estate; Residential submarket